POST- HARVEST PROCESSING OF IRRADIATION ON QUALITY PARAMETERS OF MUSHROOMS - B. KALYANI*; K. MANJULA (The Journal of Research ANGRAU, 2020)
Effect of irradiation at different doses on shelf life and quality parameters of mushrooms was studied during 2015-17. Irradiation was done by using gamma irradiation at 0.25 kGy and 0.75 kGy doses. Results of the study revealed that PLW, colour(L*, a* and b* values), moisture and fibre in mushrooms were significantly reduced among non-irradiated. Whereas, slight but insignificant changes were noticed in moisture, carbohydrate, fibre and protein content of irradiated mushrooms at 0.25 kGy. Sodium content and potassium content of mushrooms was significantly increased in all the samples.Gamma irradiation of mushrooms maintained the overall quality without determinant to their physico-chemical quality along with increased shelf life of mushrooms.